I’s Wide Shut: Examining the Depiction of Female Refugees’ Eyes and Hands in Stephen Frears’s Dirty Pretty Things - Wills, Jenny (Refuge: Canada's Journal on Refugees, 2007)
In 2002, Stephen Frears directed Dirty Pretty Things – one of the few mainstream fictional films to highlight the effects of exile, the complexities of refugee status, and the trials of migrant labour in the “Western” world. Thus far, the minimal number of “refugee” films produced is mirrored by the minimal discussion about those films (or their absence). This essay examines Frears’s film with a critical lens that incorporates both theoretical evaluations and aesthetic choices. For instance: how do media representations of refugees and migrants relegate the signification of refugee-ism to visceral, silent, repetitive, and subordinated signifiers? Additionally, this essay narrows its interest upon Senay, the female lead of Dirty Pretty Things, to open up a dialogue about fragmented body: missing hands / hyperbolized eyes. Drawing on knowledge of the theoretical implications of those choices, this paper addresses refugees and illegal migrants in film with the hope of initiating conversation about an otherwise relatively silent and untouched cinematic subgenre.